Papamal Popialicious / Hanis Arissa Mustapha ...[et al.] - Mustapha, Hanis Arissa; Omar, Fatimah; Mohd Farid, Mohamad Fikri Irhan; Mohd Noor, Ikmal Hakeem (2023)
Papamal Popialicious is a shop that sells modern versions of popiah which is Malaysia’s famous food. The product that we made is from the high quality ingredients that can attract the customers to buy the products. Our primary strategy and aim is to be a famous producer of Popia Carbonara flavours and open more branches throughout Malaysia. Our target customers are people who live around our shop since our shop is near to residential areas which are young ages, parents, students and citizens. Papamal Popialicious is basically a food industry business which offers traditional foods, such as popia with modern flavours which is Carbonara. The popia that we sell have two types, which are “Ready to eat” and the frozen ones, which you want to buy in large quantities or for whoever wants to be a dropship for our product. We are always looking for our customers' satisfaction towards our product and try to improve and maintain our product quality. Since our product is instant and easy to bring and eat anywhere, our target customer is students or parents who are busy preparing something to eat. In addition, nowadays there are many cases about food quality that can lead to food poisoning if we do not take it seriously. So we see this is our opportunity to grab chances in order to gain customers by selling high quality products. Our business is run by four main workers which are General Manager, Financial Manager, Administration Manager and Marketing Manager.